2019
DOI: 10.1039/c9ra04683f
|View full text |Cite
|
Sign up to set email alerts
|

A novel efficient bioflocculant QZ-7 for the removal of heavy metals from industrial wastewater

Abstract: In this study, a novel bioflocculant was produced using Bacillus salmalaya 139SI for industrial waste water treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…4,5 Therefore, it is signicant to completely remove HMIs from water. However, HMIs usually coexist with huge amounts of alkali or alkaline-earth metal salts and high-concentration H + in the effluents from mining, electroplating, and battery manufacturing industries, 6,7 resulting in ineffective removal by traditional technologies such as coagulation, ion exchange, and so on. [8][9][10] Recently, biomass-derived adsorbents, such as lignin, cellulose, chitosan, biochar, and so on, have shown promising potential in environmental domains mainly because of their low cost and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Therefore, it is signicant to completely remove HMIs from water. However, HMIs usually coexist with huge amounts of alkali or alkaline-earth metal salts and high-concentration H + in the effluents from mining, electroplating, and battery manufacturing industries, 6,7 resulting in ineffective removal by traditional technologies such as coagulation, ion exchange, and so on. [8][9][10] Recently, biomass-derived adsorbents, such as lignin, cellulose, chitosan, biochar, and so on, have shown promising potential in environmental domains mainly because of their low cost and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…Acid mine wastewater has become the leading environmental issue of the mining industry over the years, many methods, containing alkaline chemical neutralization, precipitation, adsorption, and membrane technology have been widely used in treatment of acid mine wastewater. However, though the utilization of biolflocculant is thought as an economic and effective strategy to treat the mining wastewater, such as clarification of turbid aqueous solutions (Liu et al, 2019), removal of organics (Maliehe et al, 2019) and metal remediation (Ayangbenro et al, 2019), probably because the flocculating activities of many reported bioflocculants have been significantly inhibited in high acidic conditions or in the presence of iron or aluminum (Tawila et al, 2019;Pu et al, 2020;Rajivgandhi et al, 2021), the application of bioflocculant in acid mine wastewater treatment is still need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional methods accomplishing chemical precipitation (Azimi et al., 2017; Fu & Wang, 2011), coagulation/flocculation (Abu Tawila et al., 2019; Verma et al., 2012), membrane filtration (Zhu et al., 2014), ultrafiltration (Huang et al., 2010), reverse osmosis (Kanamarlapudi et al., 2018; Ranitha et al., 2016), ion exchange (Thakare & Jana, 2015; Zewail & Yousef, 2015) etc. for heavy metal ions removal from wastewater have several drawbacks expensive, energy requirements, generation of toxic sludge, and inconvenient for treating low metal‐containing (<100 mg L −1 ) industrial effluents (Bethke et al., 2018; Tavker et al., 2021; Zamora‐Ledezma et al., 2021).…”
Section: Introductionmentioning
confidence: 99%